PENERAPAN NOMOR INDUK KENDARAAN BERMOTOR UNTUK MENGANTISIPASI DUPLIKASI DI REKTORAT LALU LINTAS POLDA SUMUT - Mario Carden Yunior Sihaloho; Ahmad Fauzi (JURNAL DOKTRIN REVIEW, 2023)
Motorized Vehicle Identification Number (NIK) plays a very important role in the registration/registration of motorized vehicles, because it is from this machine frame number that a vehicle's history can be known. /assembled, from which factory the vehicle was made, the type of vehicle body, the type of driving motor, the year the vehicle was manufactured and the location of manufacture/assembly of the motorized vehicle as well as the number or production serial number of the vehicle we have or will buy. The application of NIK to Regindent Then is aimed at anticipating duplication that arises from the act of disguising, hiding and/or changing motor vehicle documentswhich requires motor vehicle makers/assemblies to print NIK in one of the following ways. or body parts that are not easily replaced). Second, it is printed on the NIK plate, which is then affixed/attached permanently to an integral part of the motorized vehicle. The research method used is normative legal research. Based on the results ofthe study it was found that misuse of motorized vehicle documents which resulted in duplication not only meant falsification of motorized vehicle documents, but also the designation for the use of motorized vehicles as formulated by laws and regulations, including the relevant Minister of Industry and Trade Regulation (SNI) as stated in ( NIK) that shows the location of the area where the modification maker is domiciled. Motor vehicles which require that each component industry company must meet the following SNI requirements: First, the motor vehicle assembly industry in its production activities may use imported motorized vehicles in a completely decomposedstate (CKD) or vehicles in an incompletely decomposed state (IKD). ). Second, every motorized vehicle to be produced or imported must be registered for its type in accordance with applicable regulations.